High-Resolution Remote Sensing, In-Situ Observations, and Modeling of Low-Salinity Lenses in the Presence of Oil Slick - Soloviev, Alexander V.; Vanderplow, Breanna; Dean, Cayla W.; Schwarz, Egbert; Lehner, Susanne; Shen, Hui; Perrie, William; Schuler, Paul (International Geoscience and Remote Sensing Symposium (IGARSS), 2020)
River runoff on the Louisiana Coast produces shallow, low-salinity lenses. Due to the presence of a leaking oil platform (Taylor Energy), the fine structure of these lenses is visible in synthetic aperture radar (SAR) imagery. In this paper, we report results of the comprehensive study including high-resolution remote sensing and in-situ observations of low-salinity lenses on the Louisiana Coast as well as modeling the lens using a computational fluid dynamics (CFD) model. Our results indicate that these transient near-surface lenses create significant horizontal density gradients and spread as gravity currents, influencing the propagation of oil slicks.
CRIS-Team Scopus Importer:2024-03-18
Keywords: computational fluid dynamics; low-salinity lenses; oil slicks; river runoff; SAR